Quarantine first introduced by Ibn Sina (International Journal of Pathology, 2020)
In these days of corona virus pandemic, major emphasis is on preventive measures. The words “Quarantine” has become a household word. Very few know about its origin and the fact that its concept was first given by none other than the Final Prophet of Allah, Muhammad ﷺ . We found following article in Manila Times very relevant which we are reproducing here, thanking the author and the newspaper!1